Hero : the life and legend of Lawrence of Arabia - Korda, Michael, 1933- (Harper, 2010)
"Hero" is a definitive new biography of the legendary British scholar, adventurer, soldier, and hero who became a myth in his lifetime--T.E. Lawrence, Lawrence of Arabia.